2019
DOI: 10.1016/j.drudis.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The role of molecular simulations in understanding the mechanisms of cell-penetrating peptides

Abstract: The review discusses the simulation techniques currently being used to study cellpenetrating peptides, along with the mechanistic insights gained and challenges associated with such studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 115 publications
0
46
0
Order By: Relevance
“…Alternatively, the all-atom molecular dynamics (MD) simulations of AMPs activity would provide the ultimate level of detail in the understanding of the mechanisms of action of AMPs; however the timescale of the pathways of action of AMPs on membranes is too long (several minutes 2,16,17 ) and the numbers of peptide molecules involved in the processes excessive (as the ejections caused by Dap 31 ) to be predicted by MD simulations; these are limited to the assessment of processes shorter than a few microseconds and only a handful of peptides 45 . Consequently, even if the currently available simulations provide us with valuable insights 46 , they cannot predict unknown pathways without prior knowledge from experiments-this is the case even for pore formation 46,47 including the action of Dap 48,49 , as will be shown.…”
mentioning
confidence: 99%
“…Alternatively, the all-atom molecular dynamics (MD) simulations of AMPs activity would provide the ultimate level of detail in the understanding of the mechanisms of action of AMPs; however the timescale of the pathways of action of AMPs on membranes is too long (several minutes 2,16,17 ) and the numbers of peptide molecules involved in the processes excessive (as the ejections caused by Dap 31 ) to be predicted by MD simulations; these are limited to the assessment of processes shorter than a few microseconds and only a handful of peptides 45 . Consequently, even if the currently available simulations provide us with valuable insights 46 , they cannot predict unknown pathways without prior knowledge from experiments-this is the case even for pore formation 46,47 including the action of Dap 48,49 , as will be shown.…”
mentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have also been used to model amphipathic helix-membrane interactions of peptides and peripheral membrane proteins [12,13]. One advantage of PLOS COMPUTATIONAL BIOLOGY the MD simulations is that the dynamic nature of helix-membrane interactions are reflected in the MD trajectories.…”
Section: Molecular-dynamics-based Modeling Of Amphipathic Helix-membrmentioning
confidence: 99%
“…Molecular dynamics simulations can provide means to gain insight into the peptide/membrane interactions and various energy-independent mechanisms. A more extensive review of the molecular dynamics application for CPPs can be found in review written by Reid [ 150 ].…”
Section: Lipid Vesicle-based In Vitro Assaysmentioning
confidence: 99%